Genetic-Driven Druggable Target Identification and Validation. Issue 7 (July 2018) - Floris, Matteo; Olla, Stefania; Schlessinger, David; Cucca, Francesco
Abstract : Choosing the right biological target is the critical primary decision for the development of new drugs. Systematic genetic association testing of both human diseases and quantitative traits, along with resultant findings of coincident associations between them, is becoming a powerful approach to infer drug targetable candidates and generate in vitro tests to identify compounds that can modulate them therapeutically. Here, we discuss opportunities and challenges, and infer criteria for the optimal use of genetic findings in the drug discovery pipeline. Highlights: Analysis of the phenotypic consequences of human genetic variation is an unbiased tool to reveal molecules primarily involved in disease occurrence. A systematic search for coincident genetic associations between human multifactorial disease risk and quantitative phenotypes using genome-wide association studies (GWAS) findings is becoming an especially powerful approach to identify intermediate phenotypes controlling key checkpoints in disease pathogenesis that can be modulated therapeutically. Criteria are suggested to select optimal targets taking advantage of GWAS results and of various sources of functional and gene expression annotation. Main emerging challenges to the use of genetic data for therapeutic exploitation are also discussed.